PROFSIONALISME DAN KOMPETENSI MUTU GURU DINAS PENDIDIKAN PROVINSI JAWA BARAT - Karna Husni; Lembaga Penelitian dan Pengabdian kepada Masyarakat (Program Pascasarjana Institut Agama Islam Tasikmalaya, 2022)
Professionalism in the learning process should be a mustfulfilled for teachers in teaching. Many of these criticisms have been made by some parties,it is something that is natural to be addressed wisely and wisely by interested parties. WhereThe concept of a professional teacher will always be associated with knowledge of insight and knowledgeeducation policy, learning and learning theory, educational research (classroom action), evaluationlearning, educational leadership, classroom/school management, and technologyinformation and communication. For this reason, the role of the teacher is very demanded in determining the businessimproving the quality of formal education. It means that gum which is a learning agent must be able toorganize the learning process as well as possible, in supporting developmenteducation. Therefore, teachers need to be developed as a dignified profession, such as:what is mandated in Permandinas No. 16 of 2007 concerning Academic Qualification Standardsand Teacher Competency dated May 4, 2007. Where it is stated that teacher competency standardsdeveloped as a whole from four main competencies, namely pedagogic competence, personality,social and professional. In Law no. 14 of 2005, professional means work or activityfrom someone and become a source of income for life that requires expertise, skills, orskills that meet certain quality standards or norms and require professional education.Professional is (1) concerned with the profession (field of work based on education)certain skills); (2) requires special skills to run it; (3) requires that there bepayment for doing so. Problems and challenges in the era of globalization demand improvementquality of democratization, transparency, quality culture and human rights. IMTAQ development and accelerationScience and technology requires quality human resources who are able to go international. The free market demands all nationsto prepare quality human resources so as not to depend on other nations. Quality human resources andable to face international competition, it is only possible through proper educationMeanwhile, Indonesia is a very crucial problem in improving the quality of educationnationally, among others: 1) Mismatched teachers at various levels of education. 2) Lack of equityteachers in urban and rural areas, particularly in remote areas. 3)Government policy